Late Quaternary Environmental Change and Human Occupation of the Southern African Interior - Burrough, S (Springer, 2016)
The interior southern African basin (Kalahari) is a remarkable region, with a complex and dynamic environmental history and a long record of utilization by human populations during the late Quaternary. Paleoenvironmental reconstructions are beginning to provide a spatially detailed record of landscape and hydrological dynamics in the Kalahari, with a strong chronometric underpinning for records of environmental extremes. Theories concerning the distribution of early people in the landscape place great importance on the temporal dynamics of water availability, and may be particularly relevant in the Kalahari where there is significant evidence of hydrologic/climatic-driven landscape change. High amplitude environmental variability during MIS 6-2 is evidenced by periods of dune building within currently stabilized dunefields and the intermittent existence of large lacustrine systems such as Megalake Makgadikgadi that remain all but ephemerally dry under present-day conditions. That the wider Kalahari was, at times, a key resource for Stone Age populations is evident from the extensive occurrence of stone tools, most notably in association with the fluvial networks and lake basins of the Okavango-Chobe-Zambezi system. Today, these riparian corridors link the semiarid desert region to the southern subtropics and, in the past, drove environmental change in the Kalahari, potentially impacting the occupation and dispersal of hominins within the interior southern African basin.